1993
DOI: 10.1152/ajpgi.1993.265.2.g314
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac function and responsiveness to beta-adrenoceptor agonists in rats with obstructive jaundice

Abstract: The function and role of the heart and the contribution of cardiac beta-adrenoceptors in the pathogenesis of circulatory failure in obstructive jaundice were studied in the 3-day bile duct-ligated (BDL) rat using three different techniques to measure cardiac function and beta-adrenoceptor activity, number, and affinity. The techniques were the pithed rat preparation, the isolated working heart preparation, and a competitive radioligand binding assay for beta-adrenoceptors. The results of these experiments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
1
8
1
1
Order By: Relevance
“…This is the first report of unchanged vascular al-adrenoceptors affinity and number in a rat model of experimental cholestasis. We have previously reported that BDL of 3 days standing does not cause down-regulation of cardiac P-adrenoceptors (6). Hence, the absence of change in either affinity or number of vascular al-adrenoceptors is consistent with our earlier observations on another adrenoceptor system in other tissues in the 3-day BDL rat.…”
Section: Discussionsupporting
confidence: 91%
“…This is the first report of unchanged vascular al-adrenoceptors affinity and number in a rat model of experimental cholestasis. We have previously reported that BDL of 3 days standing does not cause down-regulation of cardiac P-adrenoceptors (6). Hence, the absence of change in either affinity or number of vascular al-adrenoceptors is consistent with our earlier observations on another adrenoceptor system in other tissues in the 3-day BDL rat.…”
Section: Discussionsupporting
confidence: 91%
“…Recorded parameters included HR, LVESP, LVEDP, (and ± dP/dt max ). Effects of propofol (12.5, 25, and 50 μmol/L) were tested using a method described by Jacob et al [18]. In rats that underwent 3-day BDL, Jacob [18] showed impaired basal cardiac contractility and reduced left intraventricular pressure using two preparations of pithed rats and isolated functioning hearts.…”
Section: Methodsmentioning
confidence: 99%
“…Effects of propofol (12.5, 25, and 50 μmol/L) were tested using a method described by Jacob et al [18]. In rats that underwent 3-day BDL, Jacob [18] showed impaired basal cardiac contractility and reduced left intraventricular pressure using two preparations of pithed rats and isolated functioning hearts. When the aortic flow and left ventricular pressure were stabilized, data were acquired for 30 consecutive seconds prior to drug testing.…”
Section: Methodsmentioning
confidence: 99%
“…Since Green et al described the cardiac injury of OJ firstly in 1986,23 studies afterwards have continuously confirmed that cardiac disfunction is one of the common complications in patients with OJ 24. Experimental studies indicated that effects of bile duct ligation on myocytes including decrease of contraction rates and amplitude leads to cardiac disfunction potentially 25. It is quite necessary to predict and intervene of MACE in the early stage of OJ operations.…”
Section: Discussionmentioning
confidence: 99%